Pros and Cons of Plastic during the COVID-19 Pandemic - Fabiula Danielli Bastos de Sousa (Recycling, 2020)
Since the beginning of the first cases of the new coronavirus, opinions and laws on the use of plastic materials have been questioned around the world. Their importance in the manufacture of hospital devices and personal protective equipment (PPE) is unquestionable, as they contribute largely to the reduction of the virus spread, helping health systems from all edges of the world and, most importantly, saving lives. However, the same material that is a protector, becomes a polluter when inadequately disposed of in the environment, generating or worsening socio-environmental problems, such as pollution of water bodies by plastic. A critical overview of the role of plastic during the COVID-19 pandemic is provided in this paper. A future panorama is attempted to be outlined. The real possibility of the virus spread from the use of plastic is discussed, as well as the recycling of plastic during the pandemic, correlating its use with problems that it may cause.